User evaluations of fabric shades with sun in the field of view: Glare model performance and implications for EN14501 Classification - Karmann, Caroline (2025)
Discomfort glare from daylight is common in workspaces, where daylight and luminance contrast between light source and background can be excessive. Fabric shadings can mitigate glare, but their light transmission properties remain difficult to characterize. This study evaluates the recommended glare classes in EN17037+A1:2022 and EN14501:2021 by analyzing data from two laboratory studies (Switzerland and Argentina) and a simulation study. The experiments involved 55 participants across 191 sessions, testing four fabrics with a low openness factor (OF<7%). Using the Osterhaus-Bailey subjective scale for glare perception, we found comfortable glare conditions (i.e., not disturbing nor intolerable) for 87-96% participants with class 3 and class 1 fabrics under the tested scenarios. However, we also found that the existing tabular classification tends to overestimate glare for fabrics with normal-normal transmittance τv, n-n larger than 0.03 are involved, as well for fabrics with lighter colors that have higher diffuse transmittances (τv, n-dif >0.03). Common glare metrics (DGP, CGI, UGP) showed strong correlations with subjective responses on the Osterhaus-Bailey scale (Spearman ρ > 0.5). DGP showed the highest correlation (ρ = 0.57) with a disturbing glare threshold of 0.43, indicating that the standard threshold of 0.40 slightly overestimates glare for shading fabrics when the sun is in the field of view. DGPmod did not perform significantly different than DGP. ROC analysis based on binary classification confirmed acceptable to excellent discrimination ability for DGP, CGI and UGP. Based on these findings and annual simulations, we recommend adjustments to the glare classification in EN14501:2021.